Economics and the price index - Afriat, S. N., 1925-; Milana, Carlo (London ; New York : Routledge, 2009)
This book brings together a coherent discussion of fifty years of astonishingly creative work on the 'The Index Number Problem'. Co-written by the leading figure in this field, it will be of interest to all those for whom the price index problem remains a source of fascination.

&#x000A
The super price index: Irving Fisher, and after -- The price level computation method -- Price level computation : illustrations -- The system of inequalities ars > Xs-Xr -- On the constructibility of consistent price indices between several periods simultaneously -- The theory of exact and superlative index numbers revisited.
Includes bibliographical references and index.
rpm 30/04/13
Loans
Keywords: Price indexes; Index numbers (Economics)